Development of a time–temperature indicator based on Maillard reaction for visually monitoring the freshness of mackerel. (30th March 2022) - Ye, Beibei; Chen, Jian; Ye, Huangwei; Zhang, Yuting; Yang, Qing; Yu, Hejun; Fu, Linglin; Wang, Yanbo
Highlights: A xylose-lysine system as the time–temperature indicator (TTI) was established. The color changes of TTI were observed within 0–25 °C during 0–10 days. The temperature and time experience of TTI can be predicted by color changes. The activation energy value (72.11 kJ/mol) of TTI was close to that of mackerel. This novel TTI could predict the contents of TVB-N of mackerel (R 2  = 0.98). Abstract: Due to the highly cost-effective and maneuverable property, Maillard reaction-based time–temperature indicators (TTIs) are considered ideal devices for temperature track and quality indication. The objective of this study was to develop a cold-sensitive TTI based on the Maillard reaction reflecting the freshness of chilled seafood. Firstly, the color evolution trends of a series of Maillard reaction-based TTIs were investigated and the xylose-lysine group represented obvious color change. Fourier transform infrared (FTIR) spectroscopy revealed the color change was associated with the formation of CN bond in melanoidin. Simultaneously, the relationships of the color change of TTI with time and temperature were established. The activation energy value ( Ea ) of TTI was close to that of mackerel. There existed a good relevance (R 2  = 0.98) between the color change of TTI and the total volatile basic nitrogen content of mackerel, suggesting this novel TTI might have the potential to monitor the freshness of mackerel.